JoJo's bizarre adventure. Part 6, Stone ocean. Volume 3 - Araki, Hirohiko, 1960- (VIZ Media LLC, 2024)
Jolyne, Ermes, and their new ally F.F.--a colony of plankton given human form and consciousness--manage to defeat the enemy Stand Mary Lynn Manson and recover Jotaro's Stand disc. The Speedwagon Foundation devises a plan to get the disc out of the prison, which involves Jolyne teaming up with another new ally, Weather Forecast. After a literally suffocating battle en route to the rendezvous point, Jolyne encounters an enigmatic priest who seems to offer salvation...